Tourism gender research: A critical accounting. (May 2015) - Figueroa-Domecq, Cristina; Pritchard, Annette; Segovia-Pérez, Mónica; Morgan, Nigel; Villacé-Molinero, Teresa
Highlights: Critiques tourism enquiry as a knowledge-generating system. Reviews the trajectory and impact of tourism gender research. Presents a bibliometric analysis of tourism gender research 1985–2012. Identifies key topics and methodologies in tourism gender research. Presents potential scenarios for future tourism gender research. Abstract: This paper seeks to rouse debate about the workings of tourism enquiry as a knowledge-generating system through its critical accounting of the sub-field of tourism gender research. This accounting includes a gender-aware bibliometric analysis of 466 journal papers published during 1985–2012, which categorises the sub-field's prevailing themes and methodologies and identifies its most prolific authors and popular journals. It contends that, despite three decades of study and a recent increase in papers, tourism gender research remains marginal to tourism enquiry, disarticulated from wider feminist and gender-aware initiatives and lacks the critical mass of research leaders, publications, citations and multi-institutional networks, which characterise other tourism sub-fields. The paper identifies two possible futures for gender-aware tourism research: stagnation or ignition.